Women autonomy and its sociodemographic correlates in high focus states of India - Patel, Vikash Singh; Patel, Sandeep; Patel, Prince Kumar (International Journal Of Community Medicine And Public Health, 2022)
Background: Autonomy is a multidimensional notion that relates to the independence or freedom of will of one's activity and is defined as the ability to receive knowledge and make judgments regarding one's issues. Women's autonomy is a function of several social, cultural, and individual factors such as education, occupation, and economic condition. To determine the socio-demographic factors influencing women’s autonomy among study subjects and to find out the contribution of these significant factors. Methods: The present study is based on the data of the 4th round of the National Family Health Survey 2015-2016 (NFHS-4). This study is based on, 381927 women of reproductive age group belonging to high focus states of India. Chi-square test and binary logistic regression analysis have been used to analyze the data. Results: In nine high focus states, Jharkhand (8.6%) is the most autonomous state while Bihar (6.4%) is the least autonomous state. Age, education, wealth index, occupation are significant factors influencing autonomy. Conclusions: Women’s age, education, working status, and the number of living children is positively associated with women’s autonomy. In high focus states, women are still struggling for their independent role in decision-making.